# `(3x + 1)/(2x^3 + 3x^2)` Write the partial fraction decomposition of the rational expression. `(3x+1)/(2x^3+3x^2)`

To decompose this to partial fractions, factor the denominator.

`2x^3 + 3x^2 = x^2(2x + 3)`

Then, write a fraction for each factor. For the repeated factor x, form a partial fraction for each exponent x from 1 to 2. And assign a variable for each numerators.

`A/x`   ,   `B/x^2`   and    `C/(2x + 3)`

Add these three fractions and set it equal to the given fraction.

`(3x+1)/(x^2(2x+3)) = A/x + B/x^2+C/(2x+3)`

To solve for the values of A, B and C, eliminate the fractions in the equation. So multiply both sides by the LCD.

`x^2(2x+3) * (3x+1)/(x^2(2x+3)) = (A/x+B/x^2+C/(2x+3)) *x^2(2x+3)`

`3x+1=Ax(2x+3) + B(2x +3) + Cx^2`

Then, plug-in the roots of the factors.

For the factor x^2, its root is x=0

`3*0+1=A*0(2*0+3) + B(2*0+3)+C*0^2`

`1=3B`

`1/3=B`

For the factor (2x + 3), its root is x=-3/2.

`3(-3/2)+1=A(-3/2)(2(-3/2)+3)+B(2(-3/2)+3)+C(-3/2)^2`

`-7/2=A(-3/2)(0)+ B(0)+9/4C`

`-7/2=9/4C`

`-14/9=C`

To get the value of A, assign any value to x, and plug-in the values of B and C to:

`3x+1=Ax(2x+3) + B(2x +3) + Cx^2`

Let x = 1.

`3*1+1=A*1(2*1+3) + 1/3(2*1+3)+(-14/9)*1^2`

`4=5A + 5/3-14/9`

`4=5A+1/9`

`4-1/9=5A`

`35/9=5A`

`7/9=A`

So the partial fraction decomposition of the given rational expression is:

`(7/9)/x + (1/3)/x^2 + (-14/9)/(2x+3)`

This simplifies to:

`7/(9x) + 1/(3x^2)-14/(9(2x+3))`

To check, express them with same denominators.

`7/(9x) + 1/(3x^2)-14/(9(2x+3))=7/(9x) * (x(2x+3))/(x(2x+3)) + 1/(3x^2)*(3(2x+3))/(3(2x+3)) -14/(9(2x+3))*x^2/x^2`

`= (14x^2+21x)/(9x^2(2x+3)) + (6x+9)/(9x^2(2x+3)) - (14x^2)/(9x^2(2x+3))`

Now that they have same denominators, let's proceed to add/subtract them.

`= (14x^2+21x+6x+9-14x^2)/(9x^2(2x+3)) = (27x+9)/(9x^2(2x+3)) = (9(3x+1))/(9x^2(2x+3))= (3x+1)/(x^2(2x+3))`

`= (3x+1)/(2x^3+3x^2)`

Therefore,  `(3x+1)/(2x^3+3x^2)=7/(9x) + 1/(3x^2)-14/(9(2x+3))` .

Approved by eNotes Editorial Team